Prevalence of Helicobacter pylori and impact of its eradication in acne vulgaris: a prospective cohort study - Shrook A Khashaba; Nagwa A Diab; Eman A Abdallah; Nora M Said (Wolters Kluwer Medknow Publications, 2020)
Background Since the discovery of Helicobacter pylori, it is linked to gastric and extragastric diseases and is proved to be associated with some dermatological diseases. H. pylori and acne vulgaris association is an interesting relation to be explored. Objective To detect the prevalence of H. pylori in acne vulgaris patients of different severities and the impact of its eradication on clinical outcome. Patients and methods A prospective cohort study, included 66 acne vulgaris patients chosen to fit into three groups according to the Global Acne Grading System: group Ι had 22 mild acne patients, group ΙΙ had 22 moderate acne patients, group ΙII had 22 severe acne patients, and group ΙV (control) had 22 healthy individuals. The patients were subjected to urea breath test, followed by anti-H. pylori immunoglobulin G detection in serum using enzyme-linked immunosorbent assay. Patients with Ab index greater than or equal to 4 were subjected to total acne lesion count before and after H. pylori triple therapy for 14 days. Results There were statistically significant increase in anti-Helicobacter immunoglobulin G index in severe acne group (P<0.001), positive correlation between antibody index and acne score (P=0.02), and statistically significant decrease in total lesion count after triple therapy in all groups (P=0.002, 0.04, 0.001), respectively. Conclusion H. pylori has a potential role in acne vulgaris and its eradication in acne patients with different severities improves the clinical outcome.